THE INFLUENCE OF BELIEFS, SOCIAL NORMS, AND SOCIAL NETWORKS ON MARKETING WITH INNOVATION AS AN INTERVENING VARIABLE (CASE STUDY: ORNAMENTAL PLANT FARMING IN TANJUNG MORAWA DISTRICT DELI SERDANG REGENCY) - Fisrika Lahagu; Syaifuddin; Yohny Anwar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to determine the effect of trust, social norms, and social networks on marketing through innovationin Tanjung Morawa District, Deli Serdang Regency. This research was conducted in Bangun Sari Village, Tanjung Morawa District, Deli Serdang Regency. the population is all ornamental plant farming farmers in Bangun Sari Village, Tanjung Morawa District, Deli Serdang Regency, namely 160 farmers. Sampling was determined using the Slovin formula and a sample of 84 farmers was determined. To determine the effect of trust, social norms, and social networks on marketing through innovation in Tanjung Morawa District, Deli Serdang Regency, statistical analysis was used with the path analysis method. The results of this study indicate that there is a direct significant effect between the variables of trust, social norms and social networks on innovation in Ornamental Plant Farming in Tanjung Morawa District, Deli Serdang Regency. Directly there is a significant influence between the variables of trust, social norms, social networks and innovation on marketing in Ornamental Plant Farming in Tanjung Morawa District, Deli Serdang Regency. Directly or indirectly the variables of trust, social norms and social networks through marketing have a significant influence on innovation, meaning that innovation can mediate between social norms and marketing.